2015
DOI: 10.1248/bpb.b14-00842
|View full text |Cite
|
Sign up to set email alerts
|

<i>Clostridium perfringens</i> TpeL Induces Formation of Stress Fibers <i>via</i> Activation of RhoA-ROCK Signaling Pathway

Abstract: Clostridium perfringens

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The other toxin gene associated with poultry is tpeL , which was also detected in ruminant and porcine strains. TpeL glycosylates cell signaling proteins resulting in apoptosis ( Guttenberg et al, 2012 ; Schorch et al, 2014 ; Nagahama et al, 2015 ) and have been shown to be responsible for increased NE pathogenicity ( Coursodon et al, 2012 ; Shojadoost et al, 2012 ; Gu et al, 2019 ). Our data indicate that the A1 beta2 toxin variant with the signal peptide is associated with avian strains, although this variant is detected in other host strains too.…”
Section: Resultsmentioning
confidence: 99%
“…The other toxin gene associated with poultry is tpeL , which was also detected in ruminant and porcine strains. TpeL glycosylates cell signaling proteins resulting in apoptosis ( Guttenberg et al, 2012 ; Schorch et al, 2014 ; Nagahama et al, 2015 ) and have been shown to be responsible for increased NE pathogenicity ( Coursodon et al, 2012 ; Shojadoost et al, 2012 ; Gu et al, 2019 ). Our data indicate that the A1 beta2 toxin variant with the signal peptide is associated with avian strains, although this variant is detected in other host strains too.…”
Section: Resultsmentioning
confidence: 99%